Morphology and Properties of Nylon 6 Blown Films Reinforced with Different Weight Percentage of Nanoclay Additives - Raghavendra R. Hegde; Gajanan S. Bhat; Bhushan Deshpande (International Journal of Polymer Science)
This article presents the effect of increasing weight percentage natural nanoclay additives on the structure, morphology and mechanical properties of nylon-6-blown films. Combination of X-ray diffraction, thermal analysis and microscopy were used to determine nanocomposite film morphology. The nanoclay additives in the films act as nucleating agent facilitates γ-crystalline forms and results in fine grained spherulite with smaller lamellar size. Increase in tensile, burst, and tear strength is observed for films with up to 5% clay loading. Even though microscale property like tensile and tear strength drops at higher add on levels, near-surface nanoscale hardness and toughness of the film keep on increasing. There is a direct correlation between nanoclay additive add on level and increase in surface energy and wetting behavior of films.